Analysing the influence of recycled concrete aggregate and expanded perlite on mortar performance - Noorsuhada Md Nor,; Ahmad Syauqi Md Hassan,; Nurul Hana Hassan Mohd Habibullah Hassan,; Soffian Noor Mat Saliah,; Amir Khomeiny Ruslan,; Amril Hadri Jamaludin,; Mohd Azrizal Fauzi,; Nor Azian Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2024)
With population growth and rapid urbanisation leading to excessive waste generation in the construction sector and the scarcity of natural resources, such as natural fine aggregates, the demand for recycled alternatives has increased. In exploring the potential of recycled materials for construction materials, the present study investigated the performance of recycled concrete aggregate (RCA) and expanded perlite in mortar as a partial replacement for fine aggregates. Different percentages of RCA and expanded perlite were used. A consistent percentage of perlite was used: 0%, 10%, 15%, 20%, 25%, 30% and 35%. The RCA and expanded perlite were then mixed with other materials such as cement, water and fine aggregate. Flowability, compressive strength and flexural strength tests were carried out. It was found that a 90% replacement of RCA for each increasing percentage of perlite in the mortar mix resulted in a significant reduction in flow diameter. The compressive and flexural strength of the mortar increased with age. However, the flexural strength of the control mortar, which contained neither RCA nor perlite, consistently exceeded that of the mortar with these additives. The results provide valuable insights for the production of new materials in the construction industry, for waste management and for lightweight yet durable construction solutions.